2021
DOI: 10.1002/nur.22162
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of emotional autonomy, problem‐solving ability, self‐efficacy, and self‐management on the glycemic control of adolescents with type 1 diabetes: A prospective study

Abstract: This prospective study tested a model to depict associations between a number of individual characteristics and 6‐month glycated hemoglobin (HbA1c) levels in adolescents with type 1 diabetes (T1D). Adolescents (N = 232) aged 10–19 years with T1D were recruited from a medical center in Taiwan. Demographic characteristics, emotional autonomy, problem‐solving ability, self‐efficacy at baseline, and self‐management information three months after baseline were collected using a self‐reported questionnaire. HbA1c le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The observed positive association between self‐efficacy and self‐care behaviours is consistent with previous findings regarding people diagnosed with T2DM alone (Lee et al., 2016). As indicated in a follow‐up study, self‐efficacy helps individuals improve their self‐care behaviours despite their frustration and the burden of living with and managing diabetes (Chen, Lo, et al., 2021). Moreover, a previous meta‐analysis revealed that self‐efficacy‐focused education substantially increased knowledge and confidence, reduced HbA1c level and improved self‐care behaviours in people diagnosed with T2DM (Jiang et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The observed positive association between self‐efficacy and self‐care behaviours is consistent with previous findings regarding people diagnosed with T2DM alone (Lee et al., 2016). As indicated in a follow‐up study, self‐efficacy helps individuals improve their self‐care behaviours despite their frustration and the burden of living with and managing diabetes (Chen, Lo, et al., 2021). Moreover, a previous meta‐analysis revealed that self‐efficacy‐focused education substantially increased knowledge and confidence, reduced HbA1c level and improved self‐care behaviours in people diagnosed with T2DM (Jiang et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the construct of self-efficacy itself, its relationship with other psychosocial variables justifies the influence it may have on diabetes management. A positive relationship was found between self-efficacy and the understanding of diabetes along with its treatment [ 16 ], which improves the quality of life in the transition to adulthood [ 17 ] and may even improve glycemic control [ 18 ]. Not least, safe environments and, above all, quality social support have proven to be very important in increasing confidence in disease management [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,4 Thus, promoting selfcare in adolescents with type 1 diabetes is key to optimise glycaemic control. [5][6][7] Self-care is defined as the 'process of maintaining health through health promoting and managing illness', according to the middle-range theory of self-care of chronic illness, 8 and comprises self-care maintenance, self-care monitoring and self-care management. 8 Self-care maintenance concerns behaviours aimed at maintaining physical and emotional stability.…”
mentioning
confidence: 99%